Local interests or centralized targets? How China's local government implements the farmland policy of Requisition–Compensation Balance. (September 2017) - Shen, Xiaoqiang; Wang, Liping; Wu, Cifang; Lv, Tiangui; Lu, Zhangwei; Luo, Wenbin; Li, Guan
Highlights: The RCBF targets conflict with local governments' interests. Detailed comparisons are made between the requisitioned farmland and the new farmland for compensation. Local governments place local interests first, farmland quantity second, farmland quality and environmental protection last. Instead of ensuring food security, the RCBF triggers environmental issues, hence entails two urgent policy shifts. Abstract: The Requisition–Compensation Balance of Farmland (RCBF) is a strict policy in China aimed at controlling farmland conversion and replenishing farmland loss caused by urban expansion through a set of top-down quotas. These conflict with local interests, since land conversion from agriculture to construction is a key tool by which local governments attract investment and raise fiscal revenue. How should local authorities respond to this centralized policy? This paper presents a framework "quantity–quality–productivity–environment" to investigate local governments' coping strategy and the holistic performance of the RCBF. The empirical study indicated that local jurisdictions placed economic and financial growth first and continued expropriating farmland on a large-scale, including land of high quality, for development. However, impelled by compulsory quotas and supervision from governments at higher levels, local authorities would partly replenish the quantity loss through farmland exploitation, regardless of the quality of the new cropland and the possible environmental impact. Consequently, fast requisition and unqualified compensation undermined the capacity of regional agricultural output. We suggest that the RCBF is not capable of guaranteeing food security, whilst farmland supplementation threatens the local environment.